A Educação de Jovens e Adultos e a Licenciatura em Educação do Campo, Artes e Música - UFT/Tocantinópolis. - Deus, Maria Keila Alves de (Universidade Federal do Tocantins, 2021)
The objective of this work is to understand what processes were necessary to arrive at the creation of the Degree Course in Rural Education, bringing through the historical context the struggle and conquests of the peasants. Public policies developed over time to address illiteracy issues in Brazil will also be elucidated; from this perspective, verify how the course deals with the issue of EJA (Youth and Adult Education) in the educator's training. The methodology used implied bibliographic and documentary sources, analysis of the PPC of the Education Course of the Campo de Tocantinópolis and interview with an open questionnaire with a teacher and student who graduated from the course in order to understand how the PPC of the Course of Education of the Countryside is structured in relation to the theme of EJA and its approach in the curriculum. As a result, we found that although the initial proposal did not attempt to discuss the EJA, during the course's implementation, actions have been taken to address the training demands for acting with the EJA.